The earliest Christian artifacts : manuscripts and Christian origins - Hurtado, Larry W., 1943- (Grand Rapids, MI : William B. Eerdmans Pub. Co., 2006)
"Much attention has been paid to the words of the earliest Christian canonical and extracanonical texts, yet Larry Hurtado points out that an even more telling story is being overlooked - the story of the physical texts themselves. He introduces readers to the staurogram, possibly the first representation of the cross, the nomina sacra, a textual abbreviation system, and the puzzling Christian preference for book-like texts over scrolls." "Drawing on studies by papyrologists and palaeographers as well as New Testament scholars - and including photographic plates of selected manuscripts - The Earliest Christian Artifacts examines the distinctive physical features of early Christian manuscripts, illustrating their relevance for wider inquiry into the complex origins of Christianity."--BOOK JACKET.
The texts -- The early Christian preference for the codex -- The nomina sacra -- The staurogram -- Other scribal features.
Includes bibliographical references (p. 193-208) and indexes.
Keywords: Christian literature, Early -- Manuscripts; Christianity -- Origin